Analisis Metode Trend Moment Sebagai Peramalan (Forecast) Penjualan UMKM Dimsum - Tessya Fakhta Tri Nasution; Arif Ridho Lubis; Alkhowarizmi (LKP Unity Academy, 2023)
Sales is a business activity that is based on a strategy or plan that is useful to increase sales of the products produced. One of the strategies developed is to predict the number of products for Micro, Small and Medium Enterprises (MSMEs). The problem that often occurs in MSMEs is the supply of the number of products that have excess stock as experienced by MSMEs Dimsum Khanzaku. This resulted in many expired products and caused considerable losses. Therefore we need a calculation in predicting the amount of inventory so that there is no excess stock that can cause losses. As for one method of data mining in forecasting or predicting is Trend Moment. In this case, the Trend Moment Method is used to forecast sales of dimsum products in the coming month using previous sales data, to find out how many products should be supplied and sold for the following month. Sales data was taken from May 2019 to April 2021. The results obtained were sales that occurred in June 2021 for a 31 Kg company, thus presenting an inaccurate prediction of only 25%. The average yield on sales from May 2021 to February 2022 is 25%.